Headmaster Technology Leadership in Malaysia Elementary Schools - Ai Yieng Wong; Khadijah Daud (Intelektual Pustaka Media Utama, 2017)
Headmaster technology leadership increasingly important in education today. This leadership, providing various positive effects to the headmaster, teachers, students and schools. Therefore, headmaster need to master this leadership to take up the leadership role of technology in schools. Based on the Headmaster Technology Leadership Model by Chang (2003), a study based on interviews conducted on 6 headmasters serving in Johor, Malaysia. This study aims to review i) the role of the headmaster in Johor as a technology leader in school ii) the challenges faced by headmaster to serve as a technology leader. Analysis of the findings from interviews found the headmaster in Johor play a role as a technology leader in the school. However, the findings have found the effort in ICT development by the headmaster in schools is different based on the needs of the school. Therefore, there is no single fixed pattern headmaster role as a technology leader. In addition, the role of the headmaster as a technology leader is not comprehensive of the five dimensions as suggested by Chang (2003). Headmaster of Johor advised to make improvements to the school led to the transformation of technology-based education.